A genomic analysis reveals the diversity of cellulosome displaying bacteria - Minor, Christine M.; Takayesu, Allen; Ha, Sung Min; Salwinski, Lukasz; Sawaya, Michael R.; Pellegrini, Matteo; Clubb, Robert T. (Frontiers in Microbiology, 2024)
Several species of cellulolytic bacteria display cellulosomes, massive multi-cellulase containing complexes that degrade lignocellulosic plant biomass (LCB). A greater understanding of cellulosome structure and enzyme content could facilitate the development of new microbial-based methods to produce renewable chemicals and materials. To identify novel cellulosome displaying microbes we searched 305,693 sequenced bacterial genomes for genes encoding cellulosome proteins; dockerin-fused glycohydrolases (DocGHs) and cohesin domain containing scaffoldins. This analysis identified 33 bacterial species with the genomic capacity to produce cellulosomes, including 10 species not previously reported to produce these complexes, such as Acetivibrio mesophilus. Cellulosome producing bacteria primarily originate from the Acetivibrio, Ruminococcus, Ruminiclostridium, and Clostridium genera. A rigorous analysis of their enzyme, scaffoldin, dockerin, and cohesin content reveals phylogenetically conserved features. Based on the presence of a high number of genes encoding both scaffoldins and dockerin-fused GHs, the cellulosomes in Acetivibrio and Ruminococcus bacteria possess complex architectures that are populated with a large number of distinct LCB degrading GH enzymes. Their complex cellulosomes are distinguishable by their mechanism of attachment to the cell wall, the structures of their primary scaffoldins, and by how they are transcriptionally regulated. In contrast, bacteria in the Ruminiclostridium and Clostridium genera produce 'simple' cellulosomes that are constructed from only few types of scaffoldins that based on their distinct complement of GH enzymes are predicted to exhibit high and low cellulolytic activity, respectively.Collectively, the results of this study reveal conserved and divergent architectural features in bacterial cellulosomes that could be useful in guiding ongoing efforts to harness their cellulolytic activities for biobased chemical and materials production.